Assessing the knowledge, attitude and practice of family planning among male population in Inaruwa Municipality of Eastern Nepal - Uprety, Samyog; Sharma, Khem Raj; Paudel, Masum; Baral, Charanidhar; Ghimire, Anup (Journal of Chitwan Medical College, 2021)
Background: Family planning allows individuals and couples to anticipate and attain their desired number of children, spacing and timing of their births. It is achieved through use of contraceptive methods. A man’s perspective on the family planning methods and services is essential on his family health. The study aimed to know about knowledge, attitude and practice of family planning methods in male (Rickshaw puller) of Eastern Nepal and to know their reasons for not using the family planning. Methods: A descriptive cross-sectional study was done in Inaruwa municipality. Total of 400 male rickshaw puller samples were taken. Knowledge, attitude and practice on contraceptives were evaluated with the help of a predesigned questionnaire. Descriptive analysis was done by using SPSS 11.5software to obtain frequencies and percentages. Results: Out of 400 interviewed, 366 were interviewed with 92% response rate, the mean age was 36.54 years, and 92.7% said they heard about Family planning method. Health worker was the main Source of family planning information. Regarding the attitude of the Male respondents, 83.1% supported the concept of family planning; only 33.9% said they had used a male contraceptive, 46.7% of the respondents said the males didn’t practice the family planning methods on themselves because of the work load. Conclusions: Majority of the respondents knew about family planning methods but only a few agreed to have used them. The main reason for men lagging behind could be that the burden of work due to which contraception in a family is taken up by females.